The Relationship between Self-Concept and Acceptance of Young Women's Physical Changes during Puberty at SMP 103 Jakarta in 2022 - Nofa Anggraini; Septiara Sulistiawati (Asian Journal of Community Services, 2023)
Puberty and adolescence are closely related to physical changes. The results of a preliminary survey conducted on 10 female students at SMP 103 Jakarta showed that some female students were not confident about the physical changes they were experiencing. The purpose of this study was to determine the relationship between self-concept and acceptance of physical changes in young girls during puberty at SMP 103 Jakarta in 2022. This research is a quantitative analytic study with a cross-sectional design. The sample in this study were young women at class VIII Jakarta 103 Middle School, totaling 78 respondents using the quota sampling technique. The research instrument used a questionnaire. The data is primary data analyzed using the chi square test. The results of the univariate analysis revealed that most of the positive self-concepts of young women were 52.6% and that acceptance of physical changes in young women was high as much as 55.1%. The results of bivariate analysis show that there is a relationship between self-concept and acceptance of physical changes in female adolescents during puberty with a p-value = 0.000.